PRICING PRACTICES BY TRADITIONAL TRADERS IN SUDIMAMPIR MARKET - Hikmahwati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the pricing strategies used by traders in Sudimampir Market, Banjarmasin, in response to the dynamics of traditional market competition. A qualitative descriptive approach was applied, with data collected through interviews with 40 traders selling various products such as clothing, fabric, prayer equipment, household goods, shoes, and bags. Primary data were obtained from interviews, while secondary data came from literature and relevant documents. The findings reveal that most traders set prices based on prevailing market rates or competitors’ prices to remain competitive. Around 70% of traders stated that their pricing aligns with the market price, and 97% believed that their selling prices reflect product quality. Regarding price flexibility, 41% of traders do not apply fixed pricing, 35% use set prices, and the rest adjust depending on the situation. These results indicate that pricing decisions are not solely profit-driven but also reflect adaptive strategies in response to market conditions and consumer perceptions.